answersLogoWhite

0


Best Answer

Simultaneous equations

-2x + y = -3

-x + 2y = 3

Multiply the bottom equation by '-2'

Hence

-2x + y = -3

2x - 4y = -6

Add the two equations

-3y = -9

Divide both sides by '-3'

y = (+)3

Substitute in to either equ'n for 'x'

-2x + 3 = -3

Subtract '3' from both sides

-2x = -6

Divide both sides by '-2'

x = (+)3

Hence (x,y) = ( 3,3)

User Avatar

lenpollock

Lvl 15
4mo ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

12y ago

x = 3 and y = 3

Form a simultaneous equation and solve by elimination.

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How do you solve -2x plus y equals -3 and -x plus 2y equals 3?
Write your answer...
Submit
Still have questions?
magnify glass
imp